Lightweight searchable medical data sharing scheme - Xinchun YIN; Mengyu WANG; Jianting NING (Tongxin xuebao)
The attribute-based encryption scheme supporting policy hiding and keyword search had a good application prospect in medical scenarios.However, most of the existing schemes did not support large attribute university or adopt the ＆quot;AND gate＆quot; structure, which limited their scalability and flexibility of access control, and many schemes could not resist offline dictionary guessing attacks.In addition, attribute-based encryption involved a large number of bilinear pairing operations, which was inconvenient for user equipment with limited computing resources.A lightweight searchable medical data sharing scheme was proposed.Based on the support for keyword search and policy hiding, a large attribute university and a linear secret sharing structure were adopted to improve the scalability and flexibility of access control.The Intel SGX was used to re-encrypt data to achieve anti-offline dictionary guessing attack.The computational overhead of decryption was reduced to a constant level, which was suitable for user equipment with limited computing resources.Finally, it is proved that the proposed scheme has the security of selecting plaintext indistinguishable and can resist offline dictionary guessing attacks.